1999
DOI: 10.1038/10147
|View full text |Cite
|
Sign up to set email alerts
|

Selective localization of cardiac SCN5A sodium channels in limbic regions of rat brain

Abstract: Voltage-dependent sodium channels have a critical role in membrane electrogenesis and repetitive firing in excitable cells. Members of this gene superfamily exhibit diffuse, tissue-specific expression in nervous, muscle and cardiac tissues 1 . Tetrodotoxin (TTX) sensitivity and resistance to zinc blockade were thought to distinguish brain from heart sodium channels, but neuronal Na + currents with heart-like properties have been found in brain 2 .Here we report selective expression of the cardiac sodium channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(95 citation statements)
references
References 15 publications
(8 reference statements)
4
88
0
3
Order By: Relevance
“…Our study represents the first detailed characterization of Na v 1.5 protein distribution in the mouse brain. Consistent with the distribution of Na v 1.5 transcripts in rat and human brain [2,12], the mouse Na v 1.5 protein was present in the limbic system, olfactory system, thalamus, and hypothalamus. However, our study revealed localization of Na v 1.5 protein in several brain regions that were not described or analyzed in previous studies.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Our study represents the first detailed characterization of Na v 1.5 protein distribution in the mouse brain. Consistent with the distribution of Na v 1.5 transcripts in rat and human brain [2,12], the mouse Na v 1.5 protein was present in the limbic system, olfactory system, thalamus, and hypothalamus. However, our study revealed localization of Na v 1.5 protein in several brain regions that were not described or analyzed in previous studies.…”
Section: Discussionsupporting
confidence: 68%
“…2d), and weak staining in the olfactory tubercule (data not shown). Meanwhile, in the limbic system where Na v 1.5 mRNA was reported to be strongly expressed [2,12], moderate Na v 1.5 immunoreactivity was detected in the nerve fibers, but no or little Na v 1.5 immunoreactivity was detected in the cell bodies in any of the limbic nuclei (Fig. 2a).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…SCN5A expression also occurs in central nervous system regions associated with the limbic system (Donahue et al 2000;Hartmann et al 1999). In zebrafish, both scn5Laa and scn5Lab are expressed in adult cardiac tissue as well as in neurons, similar to SCN5A (Fig.…”
Section: Scna Gene Expression In Teleosts and Mammalsmentioning
confidence: 93%
“…Both scn5Laa and scn5Lab were also expressed in nervous and cardiac tissues. In mammals, SCN5A is expressed in cardiac muscle and limited regions of the brain (Hartmann et al 1999;Rogart et al 1989), while SCN10A and SCN11A are expressed in peripheral nociceptive sensory neurons (Akopian et al 1996;Dib-Hajj et al 1999a;Sangameswaran et al 1996). However, mammalian expression of SCN5A, SCN10A or SCN11A has not been reported in spinal cord or eye.…”
Section: Scna Gene Expression In Teleosts and Mammalsmentioning
confidence: 99%